Accelerating Methane Reductions in Rice Production Systems through Market-based Mechanisms: Results of Farmer Surveys and Choice Experiments in Thailand - Villanueva, Donald B.; Pajadan, Karen M.; Revicoy, Riela Rose R.; Malana, Xyla Mae L.; De Castro, Allenie M.; Napasintuwong, Orachos; Duangbootsee, Uchook; Punjatewakupt, Piyawong; Mirzabaev, Alisher (International Rice Research Institute, 2025)
This report presents the results of IRRI’s farmer survey and choice experiment implemented in Thailand. The analysis documents farmers’ awareness, adoption, and preferences regarding low-emission rice cultivation practices such as alternate wetting and drying (AWD), direct seeding, rice straw management, and other climate-smart technologies. It provides detailed evidence on the level of technical support farmers receive, their incentive preferences, and the socioeconomic factors shaping their willingness to adopt methane-reducing technologies. The survey results offer a foundation for designing market-based mechanisms—particularly carbon crediting approaches—that are feasible for smallholder rice farmers in Thailand. The report concludes with policy implications for scaling low-emission practices and for improving farmer engagement in emerging carbon markets.